PENINGKATAN PANGSA PASAR RESTORAN TRADISIONAL INDONESIA MELALUI BEHAVIORAL INTENTION - SUTRISNO, NUNO; DANTI, DELFI DAYSASTRI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this study was to determine the effect of Service Quality, Perceived Value, and Customer Satisfaction on Behavioral Intention of Sederhana Restaurant Consumers in Bekasi City. The data analysis was done quantitatively and used a causal research design. The sampling method used in this study is to use Non-Probability Sampling with purposive sampling technique. All sample data obtained by distributing questionnaires totaled 146 respondents and will be processed using SPSS 25 software. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that Service Quality, Perceived Value, and Customer Satisfaction have an influence on Behavioral Intention. This research is expected to provide input or suggestions to Restaurant in Indonesia, especially Sederhana Restaurant which is the object of this research, is to be able to increase its competitiveness and market share in the food and beverage industry in Indonesia.